2003
DOI: 10.1074/jbc.m304586200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Yeast DNA 3′-Phosphatase Tpp1 and Rad1/Rad10 Endonuclease in Processing Spontaneous and Induced Base Lesions

Abstract: Tpp1 is a DNA 3-phosphatase in Saccharomyces cerevisiae that is believed to act during strand break repair. It is homologous to one domain of mammalian polynucleotide kinase/3-phosphatase. Unlike in yeast, we found that Tpp1 could confer resistance to methylmethane sulfonate when expressed in bacteria that lack abasic endonuclease/3-phosphodiesterase function. This species difference was due to the absence of ␦-lyase activity in S. cerevisiae, since expression of bacterial Fpg conferred Tpp1-dependent resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…6). The residual repair of these DSBs in this strain likely represents removal of the 3Ј phosphate by Rad1/Rad10, which has been shown to remove nonhomologous flaps in SSA (11) and to participate in the processing of 3Ј phosphates (16,33). We could not test this directly, because rad1⌬ apn1⌬ apn2⌬ tpp1⌬ yeast cells are inviable.…”
Section: Discussionmentioning
confidence: 95%
“…6). The residual repair of these DSBs in this strain likely represents removal of the 3Ј phosphate by Rad1/Rad10, which has been shown to remove nonhomologous flaps in SSA (11) and to participate in the processing of 3Ј phosphates (16,33). We could not test this directly, because rad1⌬ apn1⌬ apn2⌬ tpp1⌬ yeast cells are inviable.…”
Section: Discussionmentioning
confidence: 95%
“…Wilson and colleagues showed that Tpp1, a yeast phosphatase homolog of polynucleotide kinase, is involved in removal of the 3′ PO 4 following the repair of Top1-mediated DNA damage. Tpp1 has 3′ DNA phosphatase activity and lacks 5′ DNA phosphatase, 5′ polynucleotide kinase, and 3′ exonuclease activities; i.e., its only known activity is 3′ DNA phosphatase (24,25). We overexpressed either WT Tpp1 or a mutant Tpp1 with a change at a key catalytic residue (Asp35 mutated to Ala).…”
Section: Resultsmentioning
confidence: 99%
“…The number of identical sequences recovered is indicated for each sequence. (24) or pTW375 D35A (as pTW375, but with a Tpp1 mutation changing Asp 35 to Ala) (24) were transfected with YCplac111 that had been linearized with HindIII. Accuracy of repair of the linearized DNA was determined as described in the legend for Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the NER protein plays a NER-independent role. Similarly, flap endonuclease activity of the budding yeast Rad1p-Rad10p complex is required for removal of 3′ blocked ends from DNA strand breaks induced by reactive oxygen species (Guillet and Boiteux, 2002;Karumbati et al, 2003;Guzder et al, 2004). The S. pombe NER genes rad16, swi10 and rhp14 (XPA homolog) also have a function in msh2/pms1-independent mismatch repair (Fleck et al, 1999).…”
Section: Discussionmentioning
confidence: 99%